The failure of prisons in fostering and re-socializing prisoners - Henky Fernando (Universitas Muhammadiyah Yogyakarta, 2023)
Fostering and re-socializing prisoners lead to misconduct that results in prison failure. The studies have only concentrated on forms and factors when discussing this phenomenon, neglecting a comprehensive exploration of the implications of prison failure. This study focuses on the question,